Pseudomonas aeruginosa heteroresistance to levofloxacin caused by upregulated expression of essential genes for DNA replication and repair - Li, Wen-Ru; Zhang, Zhi-Qing; Liao, Kang; Wang, Bei-Bei; Liu, Hui-Zhong; Shi, Qing-Shan; Huang, Xu-Bin; Xie, Xiao-Bao (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa (P. aeruginosa), a common cause of severe chronic infections, has developed heteroresistance to several antibiotics, thus hindering successful treatment. In this study, we aimed to investigate the characteristics and mechanisms underlying levofloxacin (LVX) heteroresistance in P. aeruginosa PAS71 and PAS81 clinical isolates using a combination of physiological and biochemical methods, bacterial genomics, transcriptomics, and qRT-PCR. The six P. aeruginosa strains, namely PAS71, PAS72, PAS81, PAS82, ATCC27853, and PAO1, were studied. The Kirby–Bauer (K–B), minimum inhibitory concentration (MIC) test, and population analysis profile (PAP) experimental results showed that PAS71, PAS81, ATCC27853, and PAO1 were heteroresistant to LVX, with MIC of 0.25, 1, 0.5, and 2 μg/mL, respectively; PAS72 and PAS82 were susceptible to LVX with a MIC of 0.25 and 0.5 μg/mL, respectively. The resistance of PAS71 and PAS81 heteroresistant subpopulations was unstable and had a growth fitness cost. Genomic and transcriptomic results proved that the unstable heteroresistance of PAS71 and PAS81 was caused by elevated expression of essential genes involved in DNA replication and repair, and homologous recombination, rather than their genomic single-nucleotide polymorphism (SNP) and insertion-deletion (InDel) mutations. Additionally, PAS71 and PAS81 enhanced virulence and physiological metabolism, including bacterial secretion systems and biosynthesis of siderophore group nonribosomal peptides, in response to LVX stress. Our results suggest that the upregulation of key genes involved in DNA replication and repair, and homologous recombination causes unstable heteroresistance in P. aeruginosa against LVX. This finding provides novel insights into the occurrence and molecular regulation pathway of P. aeruginosa heteroresistant strains.